Alat Pendektesi Kadar NPK (Nitrogen, Phosporus Dan Potassium) pada Pupuk Organik Daun Sawit barbasis Internet of Things (IoT) menggunakan Soil NPK Sensor - Hesmi_Aria Yanti; Muhammad Alief Erfareta; Auliya Anggraeni; Alfarhad Maulana; Muhammad Ridho Hibatullah (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
Significant decline in palm oil production; this is due to the termination of fertilizer subsidies and price increases, especially NPK fertilizers. To test the nitrogen (N), phosphorus (P), and potassium (K) content and water content in organic fertilizers made from oil palm leaves, cow dung, water, and other materials. Laboratory testing using chemical analysis and a composting process for 3 months is required. The results of the analysis of N content were 1.63%, P₂O₅ was 0.16%, K₂O was 0.12%, and water content was 12.71%. These results are in accordance with the quality standards of organic fertilizers. The implementation of the NPK content detection tool in oil palm leaves uses these results as a reference. Then the implementation is carried out directly at the location by taking samples of oil palm leaves, cow dung, and water, and then testing is carried out using an integrated NPK detection tool in real time. Where the test results are N = 97 mg/kg, P = 28 mg/kg, and K = 113 mg/kg, these values ​​have not met the minimum threshold for organic fertilizer quality, so it is necessary to add other materials and incubate composting for 3 months or use EM-4 as a liquid that can help accelerate composting. The tool has an accuracy of ±2% and a resolution of up to 1 mg/kg, so the tool is suitable for use as a tool for detecting NPK levels.